2018
DOI: 10.1007/s10943-018-0626-y
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Religion and Spirituality on HIV Prevention Among Black and Latino Men Who Have Sex with Men, New York City

Abstract: The influence of religion and spirituality (R/S) on HIV prevention has been understudied, especially for Black and/or Latino men who have sex with men (BLMSM), who bear a disproportionate burden of HIV, and who are part of racial/ethnic communities with high engagement in R/S. The specific aim of this study was to explore perspectives about R/S among BLMSM to inform HIV prevention strategies and reduce HIV-related health disparities. Data from 105 qualitative interviews with BLMSM were analyzed; 58 (55%) state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 43 publications
(47 reference statements)
0
8
0
Order By: Relevance
“…Prior research has documented that Latinx sexual minority men who are religiously affiliated may experience greater internalized homophobia, which can have detrimental effects on HIV prevention and overall health [ 14 ]. While additional studies are needed to better understand the role of religion on HIV prevention in Latinx sexual minority men [ 15 ], culturally tailored HIV prevention content delivered via social media applications may provide a potential way to engage religious Latinx communities who may be deterred to access such information due to perceptions of internalized or societal stigma.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has documented that Latinx sexual minority men who are religiously affiliated may experience greater internalized homophobia, which can have detrimental effects on HIV prevention and overall health [ 14 ]. While additional studies are needed to better understand the role of religion on HIV prevention in Latinx sexual minority men [ 15 ], culturally tailored HIV prevention content delivered via social media applications may provide a potential way to engage religious Latinx communities who may be deterred to access such information due to perceptions of internalized or societal stigma.…”
Section: Discussionmentioning
confidence: 99%
“…Although research has demonstrated that spirituality and religion positively influences health, Black SMM might not be able to fully experience the social, spiritual, and health benefits associated with religious involvement due to the negative attitudes of many Black churches towards homosexuality and feelings of conflict or rejection by organized religious communities [18,[39][40][41][42]. It is possible that spiritual and/or religious supports in non-church-based settings and the use of peer support and/or peer navigators may ameliorate the negative effects of their engagement in non-affirming churches and serve as an alternative means of achieving similar benefits that others may receive through church membership.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in Black Americans have also shown positive religious coping significantly predicted medication adherence [69]. Studies have also shown mixed results with Black MSM regarding the role of religion and spirituality in HIV prevention and outcomes, with both positive and negative effects [70,71]. Further research is needed to elucidate what aspects of religion and spirituality are effective in improving HIV prevention and outcomes.…”
Section: Religion and Spiritualitymentioning
confidence: 99%